DA-DRD5 signaling reprograms B cells to promote CD8+ T cell-mediated antitumor immunity - Yuqing Wu; Lei Zhu; Sheng Li; Lu Liu; Yaman Wang; Yongbing Yang; Yuan Mu; Qiuying Zhu; Yuying Jiang; Chunyan Wu; Peiwen Xi; Chunmei Ma; et al. (Cell Reports, 2025)
Summary: Neuronal signals have emerged as pivotal regulators of B cells that regulate antitumor immunity and tumor progression. However, the functional relevance and mechanistic basis of the effects of the neurotransmitter dopamine (DA) on tumor immunity remain elusive. Here, we discovered that plasma DA levels are positively correlated with circulating B cell numbers and potently activate B cell responses in a manner dependent on the DRD5 receptor. Notably, DRD5 signaling enhanced the Janus kinase 1 (JAK1)-STAT1 signaling in B cell responses, which enhanced B cell activation and increased antigen presentation and co-stimulation, resulting in increased expansion and cytotoxicity in tumor-specific effector of T cells. Our findings demonstrate that DA signaling suppresses tumor progression and highlight DRD5 as a promising target for cancer immunotherapy.